PERANCANGAN HELPDESK TICKETING SYSTEM BERBASIS WEB - Aisyah Fatihah Amani; Fauzan Yahya; Wira Hadi Sidik; Nurhadian Nurhadian; Rivanto Bahtiar Putromi; Utami Mizani Putri (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
UTIPD often faces various problems, complaints, or requests from IT service users, when problems and complaints occur related to IT service activities, IT service users submit complaints and questions via telephone and WhatsApp, due to limited human resources and the number of complaints and questions that enter, IT staff often find it difficult to handle these problems. Therefore, a web-based helpdesk ticketing system was designed to simplify the process of reporting, assigning, resolving, and reporting complaints or requests for IT services at UTIPD. The method used in this design is RAD (Rapid Application Development) using UML (Unified Modeling Language) as a tool. The research stages include observation, interviews, literature studies, needs analysis, system design, and system implementation. This system was built using the PHP programming language and data storage using the MySQL database. The result of this research is a system that can be used to help UTIPD and IT service users in solving problems. This system is expected to improve staff performance and user satisfaction in providing and receiving IT services.